Armed conflict and schooling in Rwanda: Digging deeper - Andrea Guariso; Marijke Verpoorten (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2013)
It has been shown that armed conflict in Rwanda had a strong negative impact on schooling. Huge gaps remain, however, in our understanding of its heterogeneous effects across subgroups and the underlying mechanisms. Relying on population census data, we show that - in contrast to previous findings - there is no leveling off, i.e. the negative impact is not stronger for non-poor and boys. We further demonstrate that slower grade progression as well as increased drop-outs explain the drop in primary schooling, while the drop in secondary schooling is driven by a decline in school initiation. Finally, our results reveal a spatial mismatch between commune-level genocide intensity and the drop in schooling. We test for several confounding factors - pre-war regional trends in schooling, migration, selective killings, and post-war assistance to genocide survivors - but find that none of these factors can fully account for the mismatch. We conjecture that the impact of armed conflict on schooling in Rwanda was nationwide, both because the disruption caused by the genocide was felt in every corner of the country and because - besides the genocide - other forms of violence took place in Rwanda in the nineties.
Keywords: 330